Cu-loaded polyurethane to reduce ureteral stent microbes adherence and regulation of the inflammation response to RAW264.7 - Li, Hongwei; Zhao, Jing; Wang, Zhenyu; Hu, Jiyuan; Zhao, Jinlong; Awonusi, Bukola O.; Li, Jianzhong; Fan, Lianhui (Frontiers in Materials, 2023)
Ureteral stents blocked with encrustation is a common complication in clinic and affects bacteria colonization and inflammatory response. In this study, different concentrations of copper (0.25, 0.5, 1 1.5 and 2 g/L) were immobilized on polyurethane (PU) that showed functionalization of microbe resistance and regulation of inflammation response to RAW 264.7. The X-ray photoelectron spectroscopy (XPS), atomic force microscope (AFM) and static water contact angles are used to confirm successful immobilization of Cu on PU. The plates counting assay and observation of adhered cells by SEM demonstrated that the antibacterial performance of PU-Cu against Proteus mirabilis is dependently increased with the amount of Cu loading. Furthermore, the CCK-8 assay and apoptosis test suggested an acceptable cytotoxicity of PU-Cu in the concentration range of 0.25, 0.5 and 1 g/L. The morphology of cells observed by SEM reduced occurrence of pseudopodia after contacting with PU-Cu. Wound healing and Transwell invasion assays manifested that migration and recovery of macrophages are improved by PU-Cu. ELISA of IL-6 and IL-10 demonstrated that PU-Cu could regulate inflammatory cytokines toward anti-inflammatory functionalization.